Effects of Video-Based Group Instruction for Adolescents with Autism Spectrum Disorder. (October 2013) - Plavnick, Joshua B.; Sam, Ann M.; Hume, Kara; Odom, Samuel L.
Impairment in social interaction is a defining characteristic of individuals diagnosed with autism spectrum disorder (ASD). This can be especially challenging for adolescents as demands of social interaction increase in difficulty. Despite the need for effective social skills instruction, there are few empirically validated procedures for teaching social skills to adolescents with ASD. The present investigation evaluated the effects of a social skills training package centered around video-based group instruction (VGI) on the acquisition of complex social skills by 4 adolescents with ASD. A multiple probe across behaviors design demonstrated the effectiveness of the 3-month training package for teaching new social skills. The results suggest VGI can be an effective and efficient approach for teaching complex social behavior to adolescents with ASD.